Excise taxes and commodity promotion: Bayesian retrieval of the optimum - Holloway, G.J. (2000)
This article shows how the solution to the promotion problem - the problem of locating the optimal level of advertising in a downstream market - can be derived simply, empirically, and robustly through the application of some simple calculus and Bayesian econometrics. We derive the complete distribution of the level of promotion that maximizes producer surplus and generate recommendations about patterns as well as levels of expenditure that increase net returns. The theory and methods are applied to quarterly series (1978:2-1988:4) on red meats promotion by the Australian Meat and Live-Stock Corporation. A slightly different pattern of expenditure would have profited lamb producers.